A Novel Approach for P25‐Carbon Dot Composite and the Reactive Oxygen Species Involved in the Visible Light Photocatalytic Mineralization of Rhodamine B. Issue 35 (19th December 2017) - Mohamed Mukthar Ali, S. M. Y.; Sandhya, K. Y.
Abstract: A novel approach has been adapted for making titanium dioxide (P25)‐carbon dot composite (P25/C‐dot) and it exhibits visible light (VL) photocatalytic mineralization property towards rhodamine B (RhB). Carbonization of β‐cyclodextrin (CD) in a self‐assembled P25/β‐cyclodextrin (P25/CD) composite prepared by UV‐irradiation, using P2 O5 ‐water yields P25/C‐dot with chemical linkage between P25 and C‐dot. Photodegradation (PD) of RhB by P25/CD and P25/C‐dot were better (71%) than that of the commercial P25 (49%). Though the PD activity of both the composites was similar, the PD of RhB by P25/C‐dot follows the mineralization pathway while that in the presence of P25/CD undergoes via decolouration. Further scavenging studies reveal that hydroxyl radicals ( OH) are the dominant reactive oxygen species (ROS) in the PD of RhB by P25/C‐dot while it is superoxide anion radical (O2 −) and singlet oxygen ( 1 O2 ) for P25/CD, suggesting that OH can promote mineralization of the RhB. Our study suggests that C‐dot has a role in the formation of OH during PD reaction, catalytically or not. Abstract : A novel approach was used for the preparation of P25/C‐dot photocatalyst from a P25 and β‐cyclodextrin (CD) via a self‐assembled P25/CD composite. Though both the P25/C‐dot and P25/CD showed enhanced photodegradation of RhB under visible light, they have followed different mechanism pathway during the degradation of RhB. Photodegradation pathway by P25/CD was decolouration while it was mineralization by P25/C‐dot. Reactive oxygen species O2 − and OH, which are attributed to different pathways, are the predominant species produced by P25/CD and P25/C‐dot photocatalysts respectively.